The Building of Socialism in Platonov’s The Foundation Pit - Natalya I. Duzhina (Studia Litterarum)
The article analyzes the sequence of allegorical images in The Foundation Pit associated with the central theme of Platonov’s time, the construction of socialism. These images are united under the concept of the all-proletarian home and form a vibrant whole. The article is an attempt to understand these allegorical images as a system and to pinpoint their possible literary sources. The purpose of these multiple appearances of the all-proletarian home is to show the “building of socialism” in different aspects and from different angles. For example, as a concrete historical form (the tower being constructed in the center of the town) and in its ideal counterpart (the tower in the middle of the world); as the beginning (Nastya) and the archetype (“the shining white buildings”). These different aspects of the all-proletarian home correspond to the image of the Church in Pavel Florensky’s The Pillar and the Foundation of the Truth. In this latter work, the Church has three different incarnations: a very old holy woman (Staritza) whose age symbolizes the creation of the Church before the creation of the world; a tower under construction symbolizing the Church in its historical aspect; and a tower already built, symbolizing the Church as the only reality at the end of times. Thus, we see the Church from several perspectives. The article argues that the images of The Foundation Pit have their literary analogue in The Pillar and the Foundation of the Truth, and that the building of socialism in Platonov’s story is shown as the direct opposite of the divine Providence — God’s plan for the salvation of the world.